PEMETAAN DAN ANALISIS EFEK MULTIPLIER KOMODITAS UNGGULAN TANAMAN PANGAN DI KABUPATEN SUMEDANG JAWA BARAT - Ahmad Thoriq; Roni Kastaman (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
The agricultural sector in Sumedang district is the main source of regionaleconomic growth, thus, the development of the agricultural sector becomes the toppriority in regional development. In the context of regional autonomy, regionaldevelopment is required to prioritize leading sectors by paying attention to regionalcomparative and competitive advantages. This study aims to analyze the leadingcommodities in each sub-district in Sumedang district and the value of the prioritycommodity multiplier effects. Data analysis methods used in this study include (1)Location Quotient (LQ), (2) Differential Shift (DS), and (3) multiplier effect analysis.The results show that paddy is the main leading commodity in 9 sub-districts, followed by cassava commodity in 7 sub-districts. The multiplier effect with the largest cropping pattern of rice is found in the combination of paddy-sweet potato-paddy which is equal to 3.2 with a total farm income of Rp.196,280,606/hectare/year.